Competitive Adsorption of Cadmium(II) and Mercury(II) Ions from Aqueous Solutions by Activated Carbon from Xanthoceras sorbifolia Bunge Hull. (19th December 2016) - Zhang, Xiaotao; Hao, Yinan; Wang, Ximing; Chen, Zhangjing; Li, Chun
Abstract : This paper presents low-cost and recyclable activated carbon (XLAC) derived from Xanthoceras sorbifolia Bunge hull for high-efficiency adsorption of Cd(II) and Hg(II) ions in industrial wastewater. XLAC was prepared through H3 PO4 activation and was characterized using N2 adsorption-desorption, scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDX), and Fourier transform infrared (FTIR) spectroscopy. In single-metal-system adsorption experiments, the maximum adsorption capacities for Cd(II) and Hg(II) obtained under different experimental conditions were 388.7 and 235.6 mg·g −1, respectively. All adsorption equilibrium data fit perfectly with the Langmuir isotherm model. In a binary metal system, competitive studies demonstrated that the presence of Cd(II) significantly decreased the adsorption of Hg(II), but the adsorption of Cd(II) showed a little change in the presence of Hg(II). In addition, XLAC can be regenerated with a 0.01 mol·L −1 HNO3 solution and reused at least four times. The FTIR spectra revealed that a chemical interaction occurs between functional groups containing lone electron pairs in XLAC and metal ions. Overall, these results suggest that XLAC may be suitable as an adsorbent for heavy metal removal from wastewater streams.